Low viscosity CM-MFC

By defiberizing CMC, low-viscosity CM-MFC is produced, which solves the problems of substitution degree and viscosity limitations in the existing technology and achieves good application results in the fields of cosmetics and paper manufacturing.

CN121175463APending Publication Date: 2025-12-19SUZANO SA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202480033912.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-22
Filing Date
2024-03-22
Publication Date
2025-12-19

AI Technical Summary

Technical Problem

Existing technologies struggle to produce carboxymethylated microfibrillated cellulose (CM-MFC) with relatively low substitution and viscosity, limiting its ability to spread well and exhibit low dripping or sagging in applications.

Method used

Using a 4%-10% w/w aqueous dispersion, CMC is defibrated using a rotating disk and a stationary rotor, controlling the average fiber diameter between 0.8 μm and 8 μm to produce low-viscosity CM-MFC with a degree of substitution of 0.2-0.29.

Benefits of technology

The production of low-viscosity CM-MFC has been achieved, which is suitable for cosmetics, coatings and paper manufacturing and other fields. It provides good spreadability and rheology, while reducing pilling and improving the effectiveness of the application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121175463A_ABST
    Figure CN121175463A_ABST
Patent Text Reader

Abstract

The present invention relates to a low viscosity CM-MFC comprising a degree of substitution of 0.2 to 0.29, preferably, at 1% w / w, using an R4 rotor, at 100 rpm, a viscosity of 6700 to 9900 cP, and at 0.8% w / w, using an R4 rotor, at 10 rpm, a viscosity of 65 to 85 cP; the present invention relates to a low viscosity CM-MFC and to a method for producing a low viscosity CM-MFC, the method comprising: defibrating the resulting CMC with a rotating disk and a stationary rotor using 4%-10% w / w aqueous dispersion to obtain a CM-MFC, the defibrating degree being such that the CM-MFC fiber average diameter is between 0.8 [mu] m and 8 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present invention relates to a low viscosity CM-MFC comprising a degree of substitution of 0.2-0.29, preferably a viscosity of 6700-9900 cP at 6% w / w using R4 rotor at 100 rpm and a viscosity of 65-85 cP at 0.8% w / w using R4 rotor at 10 rpm; and to a process for producing a low viscosity CM-MFC, the process comprising:

[0002] CMC having a DS between 0.20-0.29 is defibrillated to obtain CM-MFC using a 4-10% w / w aqueous dispersion with a rotating disc and a stationary rotor to a degree of defibrillation where the average diameter of the CM-MFC fibres is between 0.8 pm to 8 pm. BACKGROUND

[0003] Carboxymethylated microfibrillated cellulose is traditionally a stable, homogeneous suspension, characterized as useful in end-use products, including food, cosmetics, pharmaceuticals, paints, and drilling muds.

[0004] Carboxymethylated microfibrillated cellulose (CM-MFC) can be used, for example, in cosmetic applications, as a thickening agent, a shape retention imparting agent, an emulsion stabilizer, or a dispersion stabilizer; in the field of cosmetics, such as setting powders, foundations, face wash scrubs, face masks, facial cleanser foams, facial cleanser creams, mousses, shampoos, soaps, lotions, hair dyes, hair bleaches, mascaras, eyeliners, nail products, and antiperspirants, without limitation. Sometimes a pilling phenomenon can occur, where the applied skin care composition detaches from the skin and forms undesirable lumps.

[0005] In the field of household products, the rheological properties of the carboxymethylated microfibrillated cellulose (CM-MFC) of the present invention and its ability to stabilize emulsions, dispersions, and foams can provide utility in areas such as detergents, shampoos, cleansers, and air fresheners. Specific examples include, but are not limited to: laundry products (including detergents, pre-stain removers, and fabric treatment compositions such as softeners); carpet and upholstery detergents; toilet bowl cleaners (particularly those dispensed in liquid or gel form); air fresheners; and, all-purpose cleaners, including liquids, gels, pastes, and foams for cleaning and / or sanitizing household surfaces.

[0006] In the papermaking and processing arts, the carboxymethylated microfibrillated cellulose (CM-MFC) of the present invention can be used for: emulsion modification and / or stabilization; sizing; retention aid; clarification; absorption; drainage; sheet formation (e.g., by acting as a flocculation aid); deposit or scale control (by inhibiting the formation and / or growth of inorganic deposits); water treatment; dewatering; film and membrane formation; polyelectrolyte crosslinking; removal of deleterious organic and / or inorganic materials; in paper coatings; and, in improving properties such as stiffness, wet strength, absorbency, softness, toughness, tear resistance, and folding endurance.

[0007] In the context of papermaking, scale control refers to the prevention of calcium carbonate and calcium oxalate deposit formation during pulping. Scale control can be achieved by dispersing salt crystals in the medium to prevent growth and deposition, inhibiting nucleation, or altering the crystal growth mechanism to prevent the formation of crystal forms that lead to deposition. The use of carboxymethylated microfibrillated cellulose (CM-MFC) with micrometer and smaller particle sizes, and stabilized with appropriate functional groups, can help control scale deposition because such microcarriers inhibit the growth of crystals that lead to deposition. Furthermore, due to its organic nature, the cellulose material will be more easily recovered from the pulping process. Preferred functional groups will include phosphate / phosphonate groups, carboxylate groups, and sulfate / sulfonate groups. Alternative functional groups and appropriate use levels can be readily determined by one of ordinary skill in the art based on the specific use environment.

[0008] The derivatized microfibrillated cellulose can also be used in paper machines to increase the rate of drainage and / or dewatering during the papermaking process; to retain organic and / or inorganic dispersed particles (such as pulp fines, fillers, sizing agents, pigments, and / or clays); to retain deleterious organic and inorganic particulate materials; to improve paper formation uniformity; and to increase paper strength. In particular with respect to drainage, drainage aids are additives that increase the rate of dewatering of the paper stock on the paper machine. These additives increase machine capacity by allowing faster sheet formation, thereby increasing profitability. Microfibrillated cellulose derivatives with anionic charge can greatly increase the rate of drainage, whether used alone or in combination with other charged polymers.

[0009] The derivatized microfibrillated cellulose of the present invention can also be used in coated papers, where the cellulose derivative can be used to control the rheology of pigment coatings and provide water retention, thereby controlling the amount of liquid penetration into the base sheet.

[0010] In coating compositions (e.g., paints and inks), the derivatized microfibrillated polysaccharides can provide rheology modification, improve properties such as spatter, leveling, sag resistance, floating and flashing, and can have particular utility in gel paints. They can also improve the dispersion and / or stabilization of pigments, and as charge control agents or flow control agents, including in inks, such as inkjet inks.

[0011] There is a need for a carboxymethylated microfibrillated cellulose (CM-MFC) having a relatively low degree of substitution and a low viscosity, which can provide, for example, good spreadability and low dripping or sagging properties.

[0012] For example, EP3126570B1 discloses a method for producing a carboxymethylated microfibrillated cellulose (CM-MFC), wherein a cellulose-based fibrous material, in which the internal bonds of the cellulose fibers are weakened by a preliminary modification of the cellulose, is subjected to a disintegration treatment by repeated successive impacts from opposite directions at a consistency of 10% to 50%. The CM-MFC has a crystallinity of 0.1 to 0.35, a degree of substitution of 0.1 to 0.2; a zero shear viscosity of 1,000 to 50,000 Pa-s, a yield stress of 1 to 50 Pa, an average diameter of 100 to 1000 micrometers, and an anionic charge of 1.00 to 1.55 mmol / g (0.33 to 0.51) when measured at a consistency of 0.5%. This document describes a method for obtaining CM-MFC at a high consistency of 10% to 50%, the fibers being carboxymethylated, the degree of substitution being between 0.12 and 0.20, and the viscosity being > 5000 cP at a consistency of 0.8% and 10 rpm. The CM-MFC of the present invention has a much lower viscosity at a consistency of 0.8% and 10 rpm, between 65 and 85 cP.

[0013] US9909256BB discloses a carboxymethylated microfibrillated cellulose (CM-MFC) having a length exceeding 1 pm, while the diameter is generally kept below 200 nm. It discloses a method for fibrillating cellulose in a homogenizer at a consistency of 1.5% to 3.5% and at a pressure of 300 to 650 bar; wherein the fibrillation is to an extent that the Brookfield viscosity is greater than 35,000 mPa-s (30,000 mPa-s at 1% consistency for 2 passes and 39,000 mPa-s at 1% consistency for 4 passes), the measurement conditions being a consistency of 0.8% and a rotational speed of 10 rpm. Furthermore, the degree of substitution of the CM-MFC is 0.6 to 1.2 mmol / g, corresponding to about 0.2-0.4. The CM-MFC of the present invention is not obtained by homogenization and has a larger size than disclosed, wherein the refining consistency is 6% and we use a rotor / stator mechanical refining, resulting in a CM-MFC having a viscosity of 65-85 cP at a consistency of 0.8% and 10 rpm, compared to 10000 cP at a consistency of 0.8% and 10 rpm for US9909256BB.

[0014] EP3951050A1 discloses a carboxymethylated microfibrillated cellulose (CM-MFC) having a degree of substitution of 0.01-0.5, a crystallinity of cellulose type I greater than or equal to 50% and in an aqueous-based medium. It discloses a CM-MFC having an average diameter of 10.0 to 150.0 pm, a viscosity of 1,000-30,000 mPa.s at 1% (w / v) (6 rpm, 25°C), a degree of substitution of 0.01-0.5 (0.1-2.5 mmol / g). Carboxymethylation of cellulose is performed by using chloroacetic acid in an alcoholic solvent. The viscosity of the CM-MFC of the invention ranges from 111.9-121.9 cP at 1% solids content, 60 rpm, 25°C, and from 65-85 cP at 0.8% solids content, 10 rpm, 25°C, compared to the viscosity of EP3951050A1 which is as high as 4000 cP.

[0015] EP2782937B1 discloses a process for manufacturing water-insoluble carboxymethylated microfibrillated cellulose (CM-MFC) wherein the degree of substitution per anhydroglucose unit is between 0.05 and 0.35 carboxymethyl groups, wherein the carboxymethylation reaction is performed at least partially at a concentration of 50% or more. Refining is disc-type or conical, concentration is between 1-30% w / v, the degree of substitution of the CM-CMF is 0.1-0.25, the loading is 0.3-0.77 mmol / g, and the zero shear viscosity measured at 0.5% concentration in water is 5,000 to 100,000 Pa.s. Cellulose fibres are treated with an alkalizing agent (sodium hydroxide) and an anionic agent (such as chloroacetic acid, preferably sodium monochloroacetate [SMCA]) to form slightly carboxymethylated cellulose having such a degree of substitution as to be insoluble in water. It discloses that the wood can be from softwood trees, such as spruce, pine, spruce, larch, spruce or hemlock, or from hardwood trees, such as birch, poplar, aspen, alder, eucalyptus or Hawaiian acacia, in chemical pulp of kraft sulfate type, the fibre diameter is 15 to 25 pm, the length is over 500 pm. The viscosity of the CM-MFC of the invention ranges from 111.9-121.9 cP at 1% solids content, 60 rpm, 25°C, and from 65-85 cP at 0.8% solids content, 10 rpm, 25°C, compared to the viscosity of EP3951050A1 which is as high as 4000 cP.

[0016] The present invention therefore provides a carboxymethylated microfibrillated cellulose (CM-MFC) having a relatively low degree of substitution and a low viscosity. SUMMARY

[0017] A first object of the present invention is a low viscosity CM-MFC comprising a degree of substitution of 0.2-0.29, preferably a viscosity of 6700-9900 cP at 6% w / w using R4 spindle at 100 rpm and a viscosity of 65-85 cP at 0.8% w / w using R4 spindle at 10 rpm.

[0018] A further object of the present invention is to provide a method for producing a low viscosity CM-MFC, the method comprising:

[0019] The resulting CMC is defibrillated using a rotating disc and a stationary rotor using a 4-10% w / w water dispersion to obtain a CM-MFC, the degree of defibrillation being such that the average diameter of the CM-MFC fibres is between 0.8 pm and 8 pm.

[0020] Preferably, the viscosity of the obtained CM-MFC is 6700-9900 cP at 6% w / w using R4 spindle at 100 rpm and the crystallinity is 38-49%. BRIEF DESCRIPTION OF DRAWINGS

[0021] Figure 1 is a MEV image of BEKP CMC used in the present invention at 500x magnification.

[0022] Figure 2 is a MEV image of BEKP CMC used in the present invention at 1,000x magnification.

[0023] Figure 3 is a MEV image of BEKP CMC used in the present invention at 5,000x magnification.

[0024] Figure 4 is a MEV image of the CM-MFC of the present invention at 15,000x magnification.

[0025] Figure 5 is a MEV image of the CM-MFC of the present invention at 15,000x magnification.

[0026] Figure 6 is a MEV image of the CM-MFC of the present invention at 40,000x magnification.

[0027] Figure 7 is a MEV image of the CM-MFC of the present invention at 40,000x magnification.

[0028] Figure 8 is an image of the CM-MFC of the present invention at 6% w / w in water.

[0029] Figure 9is a graph showing the evolution of viscosity as a function of net specific energy (kWh / t) input in the CM-MFC refining process of the present invention.

[0030] Figure 10 is a graph showing the evolution of viscosity as a function of total specific energy (kWh / t) input in the CM-MFC refining process of the present invention.

[0031] Figure 11 is a graph showing the evolution of fines x viscosity in the CM-MFC refining process of the present invention.

[0032] Figure 12 is a graphical representation of the viscosity behavior of the original CMC and the resulting CM-MFC in the present invention. DETAILED DESCRIPTION

[0033] The present invention relates to a low viscosity CM-MFC.

[0034] MFC refers to microfibrillated cellulose, which has cellulose microfibrils or bundles of microfibrils separated from cellulose-based fiber raw material. The term "fibrillation" generally refers to the mechanical disintegration of fibrous material by applying work to the cellulose fibers, in which cellulose fibrils are detached from the fibers or fiber fragments. The terms microfibrillated cellulose (MFC) and nanofibrillated cellulose (NFC) are often used interchangeably, but they are different products with different properties. Fibrillated cellulose can be classified into NFC and MFC. NFC is a nanofibrillated cellulose whose fibril length is typically up to 100 microns, and the diameter ranges from 3-100 nm. MFC is a microfibrillated cellulose whose fibrils typically have undefined length, but are usually derived from cellulose fibers having a length of 1-4 mm, such as Figure 1 、 2 and 3, the fibrillation diameter is greater than 100 nanometers. Methods for measuring the diameter and length of NFC and MFC are well known to experts in the field, and if necessary, the test methods for cellulose nanomaterials in the CSA 25100 standard are preferred for characterization. The dimensions and size distribution of the fibrils depend on the refining method and efficiency. In an aqueous dispersion, MFC typically appears as a light-colored or almost colorless gel-like material. Preferably, the MFC of the present invention is a derivatized MFC, more preferably a carboxymethylated MFC (CM-MFC). Figures 4-7 The CM-MFC of the present invention is illustrated.

[0035] Derivatization of MFC provides the CM-MFC with groups having electrostatic functionality and the degree of substitution of the derivatized microfibrillated cellulose CM-MFC of the invention can be between 0.2 and 0.29, the ionic charge between 119-136 meq / 100g, resulting in a viscosity of 6700-9900 cP at 6% w / w, using R4 rotor, at 100 rpm; a viscosity of 110-130 cP at 1% w / w, 60 rpm; and a viscosity of 65-85 cP at 0.8% w / w, 10 rpm. Figure 8 Image of the CM-MFC of the invention at 6% w / w in water.

[0036] The carboxymethylated modified fibrous material used as a starting material can be based on any plant material containing cellulose and subjected to a derivatization process to form CMC. The raw plant material can be wood. The wood can be from softwood trees, such as spruce, pine, fir, larch, Douglas fir or hemlock, or from hardwood trees, such as birch, aspen, poplar, alder, eucalyptus or Hawaiian koa, or from a mixture of softwood and hardwood.

[0037] In one aspect of the invention, the pulp is prepared from a pulp such as mechanical pulp, thermomechanical pulp, chemi-thermomechanical pulp, chemical pulp (e.g. kraft pulp, soda pulp, or sulfite pulp), bleached pulp, waste paper pulp (optionally combined with cleaning and deinking steps), steam exploded fiber pulp, or biologically (enzymatically) treated pulp. Preferably, the CMC is obtained from cellulose fibers obtained by kraft pulping.

[0038] Examples of wood pulp used to obtain CMC include mechanical pulp, thermomechanical pulp, chemi-thermomechanical pulp and chemical pulp. For example, bleached eucalyptus kraft pulp (BEKP), northern bleached softwood kraft pulp (NSBK), bleached softwood kraft pulp, bleached hardwood pulp, unbleached softwood and hardwood kraft pulp, sulfite bleached pulp, bleached chemi-thermomechanical pulp (“BCTMP”) are used to obtain MFC. Each type of pulp provides slightly different MFCs, which have different properties and sizes. Preferably, the carboxymethylated modified fibrous material CMC is from a hardwood pulp, more preferably, the CMC pulp from bleached eucalyptus kraft pulp (BEKP) is used in the invention.

[0039] The cellulose raw material comprises - into fibril bundles - fibers. When mechanically disintegrated, cellulose fibrils are separated from the cellulose bundles. In this sense, MFC (microfibrillated cellulose) is to be understood as comprising partially or completely fibrillated cellulose or lignocellulose fibers, which can be achieved by various methods known in the art. Since cellulose found in nature has a multiple hierarchical organization and orientation, the cellulose fibers comprise a layered secondary wall structure, into which macrofibrils are arranged. The macrofibrils comprise multiple microfibrils, which further comprise cellulose molecules arranged into crystalline and amorphous regions. Preferably, the cellulose used in the present invention has a crystallinity between 52% and 62%.

[0040] The fibrillated fiber material dispersion is a mixture of fiber material and water, preferably BEKP CMC and water, forming a CMC slurry. The CMC slurry can generally refer to whole fibers, parts (chips) separated therefrom, fibril bundles or fibrils mixed with water, and generally the fiber material dispersion is a mixture of these components, wherein the ratio between the components depends on the degree of processing. Preferably, the fibers are mixed with water, more preferably the fibers are CMC from a BEKP pulp, refined between 4% and 10% w / w. It can be noted that CMC allows to use higher solids content for refining compared to traditional MFC, which requires more solvent, such as water.

[0041] In one aspect of the present invention, the cellulose fibers are first derivatized and then refined. Preferably, the cellulose is carboxymethylated to a degree of substitution between 0.2 and 0.29 to provide carboxymethylated cellulose (CMC), which is then refined to a median diameter (d50) of less than 8 pm, preferably to a diameter in the range of about 0.8 pm to 8 pm. In one aspect of the present invention, the obtained CMC is refined with a total specific energy between 450 and 580 kWh / t.

[0042] In terms of general properties, the CM-CMC of the present invention has specific rheological properties, which at least include a desirable low viscosity, accompanied by a reasonable degree of substitution. Preferably, the CM-MFC of the present invention comprises a shear viscosity of 35-44 cP at 0.85% w / w, 50 rpm, has a viscosity of 6700-9900 cP at 6% w / w, using R4 rotor, 100 rpm; a viscosity of 110-130 cP at 1% w / w, 60 rpm; and a viscosity of 65-85 cP at 0.8% w / w, 10 rpm. The CM-MFC of the present invention further has a light transmittance in the range of 45% to 59% for a wavelength of 660 nm at 1% w / w; an electrical conductivity of 2.53-2.60 mS / cm.

[0043] Microfibrillation is a process in which the microfibrils of cellulose are released or partially released as individual species or small aggregates - compared to the pulp fibers before microfibrillation. A typical cellulose fiber comprises a larger aggregate of - hundreds or thousands of individual cellulose fibrils.

[0044] Typically, the MFC used in the present invention is a fibrillated cellulose comprising cellulose fibrils with a diameter less than 0.7 micrometer. Since the diameter of the cellulose fibrils depends on the origin of the wood and the fibrillation method used, MFC from different wood origins and previous treatment processes (such as pulping) can provide MFC with different properties. Examples of fibrillation include single or multi-stage refining, with high shear disintegration or release of fibrils using equipment such as refiners, grinders, homogenizers, gelatinizers, friction grinders, ultrasonic processors, single or twin screw extruders, fluidizers (such as microfluidizers, macrofluidizers, or another fluidizer type homogenizer). Depending on the method, the product can also contain fine fibers, or nanocrystalline cellulose, or other chemicals present in wood fibers or papermaking processes, for example. Preferably, mechanical fibrillation is used to obtain the CM-MFC used in the present invention. Preferably, a mechanical fibrillation method can be used, such as those disclosed in PCT WO21226693A1; subjecting CMC fibers to multiple mechanical impacts of non-cutting bars arranged in protrusions of an annular train is a preferred configuration. Two rings in high speed rotation (two rings arranged concentrically, opposite each other, with several bars on each ring as protrusions) transfer kinetic energy to the fibers, producing CM-MFC, such as the Atrex equipment. Alternative refining methods can also be employed, in which any type of refiner is used, i.e. using rotating discs and stators, to fibrillate at low, medium or high shear, to obtain the MFC used in the present invention. Preferably, the CMC used in the present invention is obtained by a refining method that operates with a net energy input between 300-450 kWh / t, to obtain CM-MFC with a diameter between 200-700 nanometers.

[0045] Figure 9 is a plot showing the evolution of viscosity in the refining process of the CM-MFC of the present invention (degree of substitution between 0.20 and 0.29) as a function of the total specific energy (kWh / t) input, Figure 10 is a plot showing the evolution as a function of the net specific energy (kWh / t) input, illustrating the increase in viscosity with the increase in energy input.

[0046] Microfibrillation can be accomplished by applying energy to the pulp under conditions sufficient to produce microfibrillated polysaccharides. The pulp can be carboxymethylated cellulose, CMC. More specifically, refining can be performed in one or more stages. For example, a cellulose pulp can be refined to a predetermined diameter, after which the material comprising cellulose is subjected to another refining, until the desired level of microfibrillation is obtained. In one embodiment, the refining can be accomplished in one step, to obtain CM-MFC for use in the present invention. In a preferred embodiment, the CMC is passed through a refiner under conditions sufficient to produce CM-MFC; these conditions can include a refining energy of at least 300 kWh / t, and the CM-MFC can be passed through the refiner one or more times, either re-fed to the same refiner or using sequentially arranged refiners.

[0047] The carboxymethylated cellulose pulp (CM-MFC) can be wet refined in the presence of water, forming a cellulose pulp suspension. Typically, the CM-MFC suspension is refined at a concentration or solids content of 4 wt.% - 10 wt.%, thereby providing CM-MFC at a concentration or solids content of between 4 wt.% - 10 wt.%.

[0048] In one aspect, the refining method is a mechanical refiner having a rotating disc and a stator. In a preferred embodiment, carboxymethyl cellulose is suspended in water and the resulting suspension is refined to produce microfibrillated carboxymethyl cellulose or CM-MFC. In one aspect, the present invention is a method for producing low viscosity CM-MFC, comprising

[0049] The resulting CMC is defibrillated to obtain CM-MFC using a rotating disc and a stationary rotor, using a 4% - 10% w / w water dispersion, to a degree of defibrillation where the average diameter of the CM-MFC fibers is between 0.8 μιη and 8 μιη.

[0050] The method of the present invention should result in CM-MFC dispersed in water. Water is the preferred liquid of the formed suspension. Enzymes can be used before, during or after fibrillation.

[0051] Preferably, the obtained CM-MFC has a viscosity of 6700 - 9900 cP (at 6% w / w, using R4 rotor, 100 rpm) and a crystallinity of 38% - 49%.

[0052] Examples

[0053] Refining CMC

[0054] CMC BEKP with a degree of substitution of 0.20-0.29 was introduced into a disc refiner DD 6700 at a concentration of 4-5% solids, the refiner having discs with a bar width of 1.5 mm, a slot width of 2.5 mm, a bar height of 4.00 mm, and an angle of 15°. The fibrillation operating temperature was 60°C, the edge speed was 200 m / s or 895 rpm, and the fibers were processed until the apparent viscosity no longer increased, typically in 15-180 minutes.

[0055] Table 1 shows the carboxylic acid content of the original CMC and the CM-MFC obtained after fibrillation of the original.

[0056] Table 1 .

[0057] Crystallization of the samples was performed by suspending the samples in distilled water, about 0.2 g of sample per portion. The suspension was then transferred to a petri dish and dried at room temperature. After drying, the thin film was peeled off and subjected to X-ray diffraction analysis.

[0058] The diffractograms of the samples were recorded using an X-ray diffractometer (Panalytical brand, Empyrean model, belonging to the IPT Housing and Construction Area Building Materials Laboratory). Cu K alpha radiation wavelength (l = 1.54 A) was used, with a Bragg angle 2 theta scan range of 5° to 30°, with a step of 0.01°. The voltage and current used were 45 kV and 40 mA. The crystallinity index of the samples sent was calculated according to the expression proposed by SEGAL et al. (1959, apud TSOUKO, 2015, p. 14844), which is: CrI = (I002- Iam / I002) · 100, where CrI is the crystallinity index, I002 is the intensity of the diffraction maximum close to the angle 2 theta = 23° (diffraction plane 002), and Iam is the intensity of the amorphous region close to the angle 2 theta = 18°-19°. The results are shown in Table 2.

[0059] Table 2 .

[0060] The viscosity of each batch was also measured. The results are shown in Table 3: Table 3 .

[0061] Other parameters were also measured as per Tables 4 and 5.

[0062] Table 4 .

[0063] Table 5 .

[0064] Figure 11 is a graphical representation of the evolution of the viscosity of the fine fibers during the CM-MFC refining process.

[0065] Table 6 shows the viscosity results comparing the initial CMC used with the obtained CM-MFC.

[0066] Table 6 .

[0067] Figure 12 is a graphical representation of these results. It can be noted that the CM-MFC is provided with a pseudoplastic behavior, which is attractive in applications where good mixability and spreadability are required, as it has a low viscosity under stress (as in wall paints), while at the same time it remains in place after application, which means a high viscosity when not stressed. In addition, when used in cosmetic applications, the formation of smearing is usually reduced due to good spreadability.

Claims

1. A low-viscosity CM-MFC containing a degree of substitution of 0.2-0.

29.

2. The CM-MFC according to claim 1, wherein, At 6% w / w, using an R4 rotor, at 100 rpm, the CM-MFC contains a viscosity of 6700-9900 cP.

3. The CM-MFC according to claim 1, wherein, At 1% w / w and 60 rpm, the CM-MFC has a viscosity of 110-130 cP.

4. The CM-MFC according to claim 1, wherein, At 0.8% w / w and 10 rpm, the CM-MFC has a viscosity of 65-85 cP.

5. The CM-MFC according to claim 1, wherein, The CM-MFC contains ionic charges between 119 and 136 meq / 100g.

6. The CM-MFC according to claim 1, wherein, The CM-MFC is from BEKP CMC.

7. The CM-MFC according to claim 1, wherein, The CM-MFC is BEKP CMC finely ground between 4% and 10%.

8. The CM-MFC according to claim 1, wherein, The CM-MFC comprises finely ground CMC with a total specific energy between 450-580 kWh / t.

9. The CM-MFC according to claim 1, wherein, At 0.85% w / w and 50 rpm, the viscosity is 35-44 cP.

10. The CM-MFC according to claim 1, wherein, At 0.1% w / w, the transmittance is 45%-59% for a wavelength of 660 nm.

11. The CM-MFC according to claim 1, wherein, At 1% w / w, the conductivity is 2.53-2.60 mS / cm.

12. The CM-MFC according to claim 12, wherein, The crystallinity of the original cellulose is 52%-62%.

13. The CM-MFC according to claim 1, wherein, The microfibrillated cellulose is obtained through a disc milling process.

14. The CM-MFC according to claim 1, wherein, The median diameter (d50) of the microfibrillated cellulose is less than 8 μm.

15. The CM-MFC according to claim 1, wherein the diameter is in the range of about 0.8 μm to 8 μm.

16. A method for producing low-viscosity CM-MFC, the method comprising the following steps: Using a 4%-10% w / w aqueous dispersion, the obtained CMC was defibrated using a rotating disk and a stationary rotor to obtain CM-MFC. The degree of defibrating was such that the average diameter of the CM-MFC fibers was between 0.8 μm and 8 μm.

17. The method according to claim 16, wherein, At 6% w / w, using an R4 rotor, and at 100 rpm, the CM-MFC of claim 19 contains a viscosity between 6700 and 9900 cP.

18. The method according to claim 19, wherein, The crystallinity of the CM-MFC is 38%-49%.

Citation Information

Patent Citations

  • Method for producing nanofibrillar cellulose and nanofibrillar cellulose product

    EP3126570B1

  • Fibrillated chemically modified cellulose fiber

    EP3951050A1

  • Process to produce microfibrillated / nanofibrillated cellulose by impacts

    WO2021226693A1